2014
DOI: 10.1016/s1995-7645(14)60017-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal relaxation of five medicinal plants used in Mexico for the treatment of several diseases

Abstract: Less polar extracts obtained from A. mexicana, T. mexicana and C. vitifolium exhibited greater relaxant effect on tracheal rat rings, which allows us to suggest them as sources for the isolation of bioactive molecules with potential therapeutic value in the treatment of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…Dentro de la última década, se han descrito tres especies mexicanas (Martínez-Gordillo & Lozada-Pé-rez 2009, Henrickson et al 2011, Turner 2013c) y se han aportado notas sobre la distribución y filogenia de algunas especies en particular (González-Gallegos et al 2015). Existen algunos avances incipientes de estudios fitoquímicos y de prospección de compuestos activos (Dimayuga et al 1991, Estrada-Soto et al 2009, Sánchez-Recillas et al 2014. …”
unclassified
See 1 more Smart Citation
“…Dentro de la última década, se han descrito tres especies mexicanas (Martínez-Gordillo & Lozada-Pé-rez 2009, Henrickson et al 2011, Turner 2013c) y se han aportado notas sobre la distribución y filogenia de algunas especies en particular (González-Gallegos et al 2015). Existen algunos avances incipientes de estudios fitoquímicos y de prospección de compuestos activos (Dimayuga et al 1991, Estrada-Soto et al 2009, Sánchez-Recillas et al 2014. …”
unclassified
“…Además, se registra un trabajo anatómico y etnobotánico de especies mexicanas (Santillán-Ramírez et al 2008). También se han realizado algunos estudios para comprender mejor los compuestos que subyacen a las propiedades aromáticas y curativas de sus especies (Hernández-Abreu et al 2011, Sánchez-Recillas et al 2014, FloresFlores et al 2016) y aquellos que podrían ser útiles en la conservación de granos y vegetales en almacenes (Juárez et al 2015). Este género aún no cuenta con un análisis que esclarezca sus relaciones filogenéticas.…”
unclassified
“…However, the full recovery of maximal Ca 2þ -induced contractions with high concentrations of calcium ( Figure 3) makes it unlike that AMEO interfere directly with the contractile proteins. Therefore, the mechanism of this effect might be a blockade of cytoplasmic membrane Ca 2þ channels, inhibiting the Ca 2þ inflow (Coelho- de-Souza et al 1997). S anchez-Recillas et al (2014 reported the relaxant effect of hexane, dichloromethane and methanol crude extracts of A. mexicana, using the rat tracheal rings as model of study.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl chavicol, linalool and D-limonene have been reported as major components of its essential oil (Estrada-Reyes et al 2004). In spite of the wide use of this medicinal plant as traditional remedy for respiratory diseases, including asthma, only one study of relaxant effect of crude organic extracts has been reported in rat trachea (S anchez-Recillas et al 2014). The present study was undertaken to investigate the relaxant effect of essential oil of A. mexicana, using the guinea pig isolated trachea rings as experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the mortality of larvae was dose-dependent and increasing concentrations of the essential oil exacerbate mortality. Probit analysis showed that LC50 and LC 90 values were calculated as 8.022% and 80.152%, respectively (Ebadollahi et al, 2013). Lopez et al (cited by Ebadollahi et al, 2013) reported estragole as an example of toxic compounds that are active against insect pests.…”
mentioning
confidence: 99%